Short Circuit Current Analysis and Recloser Coordination in 20 kV Distribution Network Using Manual Calculation and ETAP Software Simulation - Riswanda; Putri, Raihan; Abdul Muthalib, Muchlis (Universitas PGRI Adi Buana Surabaya, 2025)
This study aims to analyze the performance of reclosers in improving the reliability of the 20 kilovolt distribution network at PT PLN (Persero) UP3 Lhokseumawe. The research focuses on optimizing the placement and delay time settings of reclosers based on fault current and network impedance. A comparative method was used involving manual calculations and simulation using ETAP 16.0.0 software. The object of study is the CD 12 feeder. The simulation evaluates fault currents and the corresponding recloser delay times at several bus locations. Results show that the closer the fault location to the power source, the higher the short-circuit current, which leads to shorter recloser operating time. Conversely, longer distances result in lower fault currents and longer delay settings. The analysis confirms that proper coordination and parameter settings significantly improve system protection and recovery. Moreover, differences between manual and simulation results emphasize the importance of digital tools in distribution network analysis. The study concludes that recloser configuration based on accurate load profiles and fault data enhances overall system performance and operational efficiency.